2015
DOI: 10.1016/j.niox.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrogen sulfide in skeletal muscle biology and metabolism

Abstract: Hydrogen sulfide (H2S) is a novel endogenous gaseous signal transducer (gasotransmittor). Its emerging role in multiple facets of inter- and intra-cellular signaling as a metabolic, inflammatory, neuro and vascular modulator has been increasingly realized. Although H2S is known for its effects as an anti-hypertensive, anti-inflammatory and anti-oxidant molecule, the relevance of these effects in skeletal muscle biology during health and during metabolic syndromes is unclear. H2S has been implicated in vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 70 publications
1
28
0
Order By: Relevance
“…A consistent hallmark of H 2 S exposure that has been well characterized is the inhibition of cytochrome c oxidase (complex IV) of the electron transport chain . Our model recapitulates this biochemical effect: cytochrome c oxidase activity was significantly decreased on all days of H 2 S exposure in both male and female mice.…”
Section: Discussionsupporting
confidence: 70%
“…A consistent hallmark of H 2 S exposure that has been well characterized is the inhibition of cytochrome c oxidase (complex IV) of the electron transport chain . Our model recapitulates this biochemical effect: cytochrome c oxidase activity was significantly decreased on all days of H 2 S exposure in both male and female mice.…”
Section: Discussionsupporting
confidence: 70%
“…Limb ischaemia and reperfusion occurs when tissue is reperfused following a period of ischaemia, which is commonly encountered in surgical pathology, especially in peripheral vascular surgery that requires longer time and intraoperative blood flow . The process of lower limb IRI usually leads to degeneration, necrosis, or apoptosis of skeletal muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Limb ischaemia and reperfusion occurs when tissue is reperfused following a period of ischaemia, which is commonly encountered in surgical pathology, especially in peripheral vascular surgery that requires longer time and intraoperative blood flow. [8][9][10] The process of lower limb IRI usually leads to degeneration, necrosis, or apoptosis of skeletal muscle tissue. The current studies have shown that the IRI of skeletal muscle affects many different organ systems, including the heart, lung, and intestine, and there are several limitations in the clinical treatment of skeletal muscle ischaemia of perfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…SQOR is a protein coding gene that may interact with the inner mitochondrial membrane in a monotopic fashion and catalyze the mammalian metabolism of H2S (hydrogen sulfide) in human [19]. Veeranki and Tyagi et al [20] proposed a model where H2S may function in skeletal muscle wasting/fibrosis as a result of metabolic complications (such as from obesity), which implied that the features of H2S reversed muscle damage…”
Section: Wssgwas For Bwmentioning
confidence: 99%